DESKRIPSI MEDIA YANG DIGUNAKAN GURU DALAM PEMBELAJARAN TEMATIK MELALUI PLATFORM WHATSAPP KELAS V - Ningrum, Lisa Eka; Kresnadi, Hery; Suparjan, Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this research is to describe:(1) The teacher using whatsapp platform as a media in thematic learning, (2) whatsapp platform appropriate to used as media in thematic learning at fifth grade of SDN 26 Pontianak Tenggara. This research is using qualitative method with descriptive method with the data sources come from the fifth greader's teachers accompanied with the lesson. The data technique is using interviews, documentation and reading note techniques. The data analysis in this research using the data collection, data reduction, presentation data and verification/drawing conclusions. The results showed that (1) the teacher using an audio, audiovisual and digital device from whatsapp platform as a media in thematic learning, (2) the teacher using a appropriate media proven by interview sheet results of the teacher and three of the fifth grader student accompaines with a screencapture from the whatsapp group, with design of lesson implementation as a support.